Promising photocatalysts based on nanoshaped TiO2 - rGO composite doped with metals (Pt and Cu) for hydrogen photoproduction. Issue 6 (December 2022) - Pollap, Aleksandra; Serafin, Jarosław; Serrano, Isabel; Sreńscek-Nazzal, Joanna; Llorca, Jordi
Abstract: Photocatalysts based on TiO2 and its modification have become popular as promising materials for the sustainable photoproduction of hydrogen. In this work, novel Pt - Cu - TiO2 composites with different TiO2 nanoshapes and modified with biomass-derived reduced graphene oxide (rGO) are reported as promising photocatalysts for the generation of hydrogen from water-alcohol mixtures. The developed photocatalyst has been characterized by X-ray diffraction, X - ray fluorescence spectroscopy, Raman and Fourier-transform infrared spectroscopies, scanning electron microscopy and Brunauer-Emmett-Teller surface area analysis. The partial replacement of platinum with copper definitely lowered the cost of hydrogen photoproduction still keeping its high efficiency. Furthermore, the additional modification of the composite with rGO successfully boosted the amount of generated H2, which was ca. 27 mmol h −1 g −1 . Graphical Abstract: ga1 Highlights: A new TiO2 -rGO composite decorated with metals for H2 photoproduction is proposed. The Influence of TiO2 shape on the photocatalytic process is verified. Synthesis and application of biomass-derived rGO as catalyst modifier is reported Reducing the Pt content through Cu reduces the catalysis cost The highest H2 production (27 mmol h −1 g −1 ) is found for 0.5 %Pt-0.5 %Cu-2 %rGO-TiO2